The Relationship Between Oral Cavity Microbiome and Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article examines the disorders of the oral microbiota as a result of endogenous and exogenous influences, its effect on internal organs and related diseases. Although modern medicine increasingly recognizes the co-evolutionary role of the microbiome in human health, the oral microbiome remains a complex system that plays an important role in maintaining health and well-being. In healthy individuals, the oral microbiota maintains a symbiotic balance with the host organism, where pathogenic bacteria exist in small numbers that are not clinically significant.Nevertheless, external influences from the environment can easily disrupt the oral microbiome, leading to a dysbiotic state with an incorrect balance and diversity of microorganisms in the mouth. This environmental impact is a risk factor that can largely be controlled. Increasing evidence suggests that problems with the oral microbiota are not only limited to local effects but also can affect the risk of other chronic diseases, such as diabetes, atherosclerotic heart disease, and rheumatoid arthritis.